2017
DOI: 10.1186/s13048-017-0329-0
|View full text |Cite
|
Sign up to set email alerts
|

WAP four-disulfide core domain protein 2 promotes metastasis of human ovarian cancer by regulation of metastasis-associated genes

Abstract: BackgroundWAP four-disulfide core domain protein 2 (WFDC2) shows a tumor-restricted upregulated pattern of expression in ovarian cancer.MethodsIn this study, we evaluated the role of WFCD2 in tumor mobility, invasion and metastasis of ovarian cancer in clinical tissue and in ovarian cancer cells, both in vitro and in vivo.ResultsOur results revealed WFCD2 was overexpressed in ovarian tissues, and the expression level of WFCD2 was associated with metastasis and lymph node metastasis. Higher expression of WFCD2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…MMP-2 and MMP-9 are two important members of MMP family 25. A high expression level of MMP-2 and MMP-9 is found in many types of cancer, such as ovarian, cervical, hepatocellular, head and neck and thyroid, and squamous cell carcinomas 26,27. In our study, the overexpression of KCNK15-AS1 decreased the levels of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 61%
“…MMP-2 and MMP-9 are two important members of MMP family 25. A high expression level of MMP-2 and MMP-9 is found in many types of cancer, such as ovarian, cervical, hepatocellular, head and neck and thyroid, and squamous cell carcinomas 26,27. In our study, the overexpression of KCNK15-AS1 decreased the levels of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 61%
“…To further confirm the correlation with WFDC2 and MMP-2, we also examined the expression of WFDC2 and MMP-2 in clinical samples with IHC and did the correlation assay. As shown in Figure 1D, a positive correlation between MMP-2 and WFDC2 expression was observed in 100 ovarian cancer patients (tumor characteristics for ovarian cancer patient see in Table S1 or reference21).
Figure 1 WFDC2 knockdown suppressed the expression of MMP-2.
…”
Section: Resultsmentioning
confidence: 76%
“…Previous data have shown that WFDC2 knockdown significantly attenuates migration and invasiveness of ovarian cancer cells 5,21. MMPs, especially MMP-2 and MMP-9, can degrade the ECM to regulate cell migration and invasion 1621.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The median (pct 25-75 ) follow-up time was 21 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) months. In the present analysis we used the 1,611 patients who had both HFrEF (defined by HF and a LVEF ≤40%) and circulating biomarkers measured.…”
Section: Index Cohortmentioning
confidence: 99%